2012
DOI: 10.1097/mpg.0b013e31824e5f95
|View full text |Cite
|
Sign up to set email alerts
|

Inulin and Fructo‐oligosaccharides for the Prevention of Antibiotic‐associated Diarrhea in Children

Abstract: T o the Editor: We provided care to a 10-year-old girl who had placed 2 Buckyballs magnets in her mouth as a makeshift tongue ring, and accidentally swallowed both magnets. An emergent esophagogastroduodenoscopy revealed that the magnets had passed beyond the duodenum. After 48 hours of conservative management, the magnets appeared to remain in a static position in the right lower quadrant. A limited noncontrast computed tomography scan of the abdomen showed both magnets attached to each other in the appendix.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…9 Evidence for the benefit of prebiotics for these conditions is more limited, and of these conditions, prebiotics may benefit those with IBS the most. [10][11][12][13][14] While some research supports the use of probiotics and prebiotics for these conditions, not all data support use of these dietary supplements. 15 More randomized controlled trials should be conducted to determine optimal dosage, strain (probiotics), and composition (prebiotics) for each condition, as well as determine the effectiveness of these dietary compounds on additional conditions such as metabolic diseases including cardiovascular disease and diabetes.…”
mentioning
confidence: 99%
“…9 Evidence for the benefit of prebiotics for these conditions is more limited, and of these conditions, prebiotics may benefit those with IBS the most. [10][11][12][13][14] While some research supports the use of probiotics and prebiotics for these conditions, not all data support use of these dietary supplements. 15 More randomized controlled trials should be conducted to determine optimal dosage, strain (probiotics), and composition (prebiotics) for each condition, as well as determine the effectiveness of these dietary compounds on additional conditions such as metabolic diseases including cardiovascular disease and diabetes.…”
mentioning
confidence: 99%
“…The Global Recommendations of the World Gastroenterology Organization (2017) align with the above regarding the types of probiotics to be used. Finally, an ESPGHAN report on the use of inulin and fructo-oligosaccharides in 2012 showed that they were not effective treatments [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding current trends on the different uses of biotics in diseases, the present review highlighted a variety of important fields, such as the administration of probiotics in the context of acute infectious diarrhea [ 17 , 51 , 52 ], nosocomial diarrhea [ 20 , 21 , 52 , 57 ], diarrhea associated with antibiotics [ 22 , 23 , 51 , 53 , 59 , 60 ], functional abdominal pain [ 53 , 64 ], pouchitis [ 53 ], and necrotizing enterocolitis in infants [ 53 ], as well as their role as adjuncts in ulcerative colitis [ 52 ], in the improvement in the eradication rate of H. pylori [ 24 , 25 , 26 ], and as prevention tools for allergic disease in infants [ 34 , 37 ]. Emerging fields include neurodevelopmental disorders [ 36 , 37 , 38 ], obesity [ 40 ], otitis media [ 42 ], and viral respiratory infections [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, an ESPGHAN study conducted among infants and children aged 6 months-11 years who were given antibiotics with 5 g per day of FOS and inulin failed to show any significant effect on AAD when compared to the placebo group. There is a need for further large-scale systematic studies to clearly elucidate the role of FOS in preventing AAD in infants and children [27].…”
Section: Fos In Preventing or Reducing Antibiotic-associated Diarrhea...mentioning
confidence: 99%